Speculation and Economic Stability - Kaldor, Nicholas (Review of Economic Studies, 1939)
Journal Article Speculation and Economic Stability Get access Nicholas Kaldor Nicholas Kaldor London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 7, Issue 1, October 1939, Pages 1–27, https://doi.org/10.2307/2967593 Published: 01 October 1939